Evaluation of models for decision making in inspection and repair maintenance - Coxon, W D (Department of Mechanical Engineering, 2016)
There has been growth in the costs of maintenance over the last 40 years. This can be linked directly to the changes in production technology over that period of time. However. there has also been growth in the field of management science and operations research. Many models have been developed to assist the maintenance function in its decisions. However. it would appear from engineering journals and shop floor practice that these models are not well used. For this research the method of inspection and repair maintenance has been chosen. Mainly because it is one of the most widely used methods. The objectives of the research are as follows: (1) To investigate the state of the art of plant and equipment maintenance paying particular attention to the inspection and repair policy. (2) To establish what basic models are available for decision making in inspection and repair maintenance. (3) To establish how feasible and useful each of these models is in the practical engineering environment. (4) To consider factors in the implementation of a decision making model in the inspection and repair policy with particular reference to the most practical and feasible model investigated.